Genome Sequence of Pseudomonas putida S12, a Potential Platform Strain for Industrial Production of Valuable Chemicals - Tao, Fei (American Society for Microbiology, 2012)
Pseudomonas putida strain S12, a well-studied solvent-tolerant bacterium, is considered a platform strain for the production of many chemicals. Here, we present a 6.28-Mb assembly of its genome sequence. We have annotated 32 coding sequences (CDSs) encoding efflux systems of organic compounds and 195 CDSs responsible for the metabolism of aromatic compounds.